Vegetable disseases : - Koike, Steven T. (Academic Press, 2007)
This book focuses primarily on diseases that are caused by pathogens. Chapters dealing with the general principles of the causes, diagnosis and control of vegetable crop diseases are followed by crop-based chapters. Each disease entry includes a brief introduction to the disease, detailed description of disease symptoms, information on the pathogen and disease development, and suggestions on how to manage the problem. Top quality color photos illustrate the book throughout. This book will be useful to a range of professionals including research and extension plant pathologists; diagnosticians and plant lab personnel; teachers of agriculture and related subjects; university students in agriculture and related fields; commercial farmers, vegetable producers, and farm managers; agriculturalists in the fields of seed production, vegetable breeding, agrichemicals, pest control, marketing, and other subjects; government and regulatory persons dealing with agriculture; serious gardeners and hobbyists